The Influence of Country of Origin, Brand Association, and Brand Loyalty on Purchase Intention and Strategies to Increase Buying Interest in Skincare Products - Netasari Khadijah; Alim Setiawan Slamet; Ma'mun Sarma (LP2M IAIN Palopo, 2026)
The cosmetics industry is one of the leading businesses in the world and is mainstream in the global cosmetics industry. In line with the development of the world cosmetics market which is still showing positive growth, the Indonesian cosmetics industry has also shown an acceleration of growth in recent years. One of the impacts of current trends is that consumers' purchasing decisions are not only influenced by factors such as quality, price, and design, but also influenced by the brand name and country of origin. The purpose of this study is to analyze the influence of country of origin, brand association, and brand loyalty on the purchase intention of local and non-local (imported) skincare products and also formulate recommendations for strategies that can be done to increase consumer buying interest in local skincare products. In this study, the researcher used four methods, namely descriptive analysis, SEM-PLS, AHP, and SWOT.